EVALUATION OF THE MAJOR HYDROGRAPHIC AND PHYSICAL CHEMICAL CHARACTERISTICS RELATED TO THE QUALITY OF THE MARINE MULTIDIMENSIONAL SCALING - Adriazola Cruz, Rosa Ysabel (2010)
Multidimensional scaling is a statistical method for analyzing dataassociated with a set of procedures aimed at the representation of data through aconfiguration of points where certain information is known about similarities betweenobjects. The history of multidimensional scaling methods begin with the work ofTorgeson in 1952, who introduced the ierm and sketched the first ideas. In this paperwe describe the main concepts arourul this issue and we need its conceptual aspects.An application to a problem regarding the physical and chemical hydrographic featuresrelaied to the Peruvian marine samples of the possibilities of multidimensional scaling.